Red Diffuse Light Suppresses the Accelerated Perception of Fear. - West, Greg L.; Anderson, Adam K.; Bedwell, Jeffrey S.; Pratt, Jay (Psychological Science., 2010)
A study examined whether the fast propagation along the dorsal action pathway drove an accelerated conduction of fear based content. Data were obtained through employing a visual prior entry procedure by assessing accelerated stimulus perception while by either suppressing the magnocellular pathway with red diffused light or leaving it unaffected with green diffused light. Findings revealed that the encoding of fearful faces was accelerated, but not when magnocellular channel activity was suppressed. Findings indicated, therefore, a dissociation that implies a privileged neural link between emotion and action that starts at the retina. Findings are discussed in detail.